1997
DOI: 10.1300/j031v08n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Employment Discrimination Against Older Workers

Abstract: Pairs of resumes, one for a 57-year-old and the other for a 32-year-old, were mailed to 775 large firms and employment agencies across the United States. Although the resumes presented equal qualifications, the older job seeker received a less favorable employer response 26.5% of times when a position appeared to be vacant. Vigorous enforcement of equal opportunity laws as well as initiatives to change employer attitudes are appropriate responses to such discrimination. The technique of employment testing, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(30 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…For instance, mixed-age teams maximize older workers’ duration of employment, and at least one audit study has found that lower levels of an organization’s age-discriminatory hiring practices correlate with higher levels of its overall success (Bendick et al, 1997; Centre for European Economic Research/ZEW, 2013). Nevertheless, approximately 60 percent of workplaces report intergenerational conflict (per a recent survey; Murphy, 2007), presenting managerial challenges for those attempting to reap the benefits of multiple-aged workplaces.…”
Section: An Uncharted Policy Issue: Intergenerational Workplace Intermentioning
confidence: 99%
“…For instance, mixed-age teams maximize older workers’ duration of employment, and at least one audit study has found that lower levels of an organization’s age-discriminatory hiring practices correlate with higher levels of its overall success (Bendick et al, 1997; Centre for European Economic Research/ZEW, 2013). Nevertheless, approximately 60 percent of workplaces report intergenerational conflict (per a recent survey; Murphy, 2007), presenting managerial challenges for those attempting to reap the benefits of multiple-aged workplaces.…”
Section: An Uncharted Policy Issue: Intergenerational Workplace Intermentioning
confidence: 99%
“…A qualitative summary of organizations that have made older workerfocused changes, such as altering ergonomics and targeting older worker-specific skills, indicates bottom-line gains in both profits and employee retention (North & Hershfield, 2014). Moreover, those who successfully avoid agediscriminatory hiring practices experience higher levels of overall success-in terms of employment desirability, industry reputation, and sales and profits rankings (Bendick, Jackson, & Romer, 1997). However, at the same time, older workers are statistically more likely to become disabled and therefore protected by ADA, which presents potential costs down the road, and contributes to reluctance among employers to hire them (Neumark, Song, & Button, 2015).…”
Section: A Practical Need To Accommodate Older Workersmentioning
confidence: 99%
“…Another potential limitation is that audit studies focus on entrylevel jobs (where employers are unlikely to conduct extensive background checks on applicants): An older worker who is (still) applying for low-level jobs may be considered as having revealed low potential, whereas applications by younger workers may be regarded as typical of early career stages (Lahey 2008). Despite these complications, several studies have studied age discrimination using audit designs and practically all of them conclude that older workers face substantial discrimination in the hiring process (Bendick et al 1997(Bendick et al , 1999Rich 2006, 2007a,b;Lahey 2008).…”
Section: Age Discrimination and Feedback Effects Of Retirement Patternsmentioning
confidence: 99%